Computational and experimental pore-scale studies of carbonate rock samples for the brazilian pre-salt scenario - Silva, William Godoy de Azevedo Lopes da (2019)
Coquinas, from the pre-salt reservoirs in the Santos Basin off the southeast coast of Brazil, are examples of carbonate rocks where much attention has focused on proper characterization of its petrophysical and multiphase flow properties. Since it is very difficult to obtain rock samples from these very deep reservoirs, analogues from northeastern Brazil are often used because of very similar geological age and petrophysical properties. Coquina plugs were collected from an outcrop in a quarry in northeast Brazil and a comprehensive set of analysis were performed. This included Scanning Electron Microscopy (SEM), Energy-Dispersive X-ray Spectroscopy (EDS), X-ray Diffraction (XRD), Nuclear Magnetic Resonance (NMR), micro-computed tomography (μCT) image acquisition using a series of pixel sizes, direct absolute permeability/porosity measurements, and centrifuge methods for capillary pressure measurements. Results included the carbonate rock composition and pore systems at different scales, thus allowing the reconstruction and modelling of porosity and absolute permeability of coquina samples based on 3D digital reconstruction and numerical simulations using pore network models (PNMs). The results provided critical information about the pore system of the coquina carbonate rock, and improved methods for predicting single- and twophase flow through the pore networks.